2008
DOI: 10.1021/nl072658h
|View full text |Cite
|
Sign up to set email alerts
|

MspA Porin−Gold Nanoparticle Assemblies: Enhanced Binding through a Controlled Cysteine Mutation

Abstract: In this study, the interactions of two gold nanoparticles of different sizes (average diameters of 3.7 +/- 2.6 and 17 +/- 3 nm) with octameric mycobacterial porin A from Mycobacterium smegmatis (MspA) and a mutant of MspA featuring a cysteine mutation in position 126 (Q126C) are investigated. From the observation of enhanced photoluminescence quenching, it is inferred that the presence of eight cysteines in the MspA Q126C mutant significantly enhances the binding of selected small gold nanoparticles within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…In a previous study we generated a series of small Au NPs with an average diameter of 3.7 nm, and a series of larger Au NP with an average diameter of 17 nm 16. Furthermore, HPLC-experiments demonstrated that the binding of both the small and large NPs to MspA in solution occurs with very high binding constants (K B >10 9 M −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we generated a series of small Au NPs with an average diameter of 3.7 nm, and a series of larger Au NP with an average diameter of 17 nm 16. Furthermore, HPLC-experiments demonstrated that the binding of both the small and large NPs to MspA in solution occurs with very high binding constants (K B >10 9 M −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on experiences in inhalation toxicology, a series of tests was proposed for evaluation of the toxicity of nanoparticles used in drug delivery systems [6]. GNPs can easily enter cells, and the demonstration that amine and thiol groups bind strongly to GNPs has enabled their surface modification with amino acids and proteins for biomedical applications [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Hence, in our investigation, there is evidence to indicate that excess cortisol levels co-exist with serotonin-selective pathologies, as ASD and treatment with AuNPs in group TADcaused no significance changes in either cortisol or serotonin relative to controls (Table 3). Gold nanoparticles (AuNPs) can easily enter cells [68]], and the finding that amine and thiol groups bind strongly to AuNP has led to their surface modification with amino acids and proteins for biomedical applications [69]. …”
Section: Discussionmentioning
confidence: 99%